Genetic diversity and prevalence of porcine circovirus type 3 (PCV3) and type 2 (PCV2) in the Midwest of the USA during 2016–2018. Issue 3 (16th January 2020) - Wang, Yin; Noll, Lance; Lu, Nanyan; Porter, Elizabeth; Stoy, Colin; Zheng, Wanglong; Liu, Xuming; Peddireddi, Lalitha; Niederwerder, Megan; Bai, Jianfa
Abstract: In recent years, reports indicated that PCV3 may be involved in porcine dermatitis and nephropathy syndrome (PDNS)‐like disease similar to that linked to PCV2. A total of 2, 125 porcine samples from 910 cases were collected during 2016–2018 and tested for presence of PCV3 and PCV2 by real‐time PCR assays. Results showed high prevalence of PCV3 and PCV2: 28.4% samples from 41.2% cases were PCV3 positive and 16.4% samples from 16.7% cases were PCV2 positive. The overall coinfection rate was 5.4% and 8.4% at the sample and case level, respectively. Temporal analysis indicated that PCV3 positive case rate increased from 31.6% in 2016, 40.9% in 2017, to 55.6% in 2018. Although its prevalence was lower, PCV2‐positive case rate in 2018 (28.8%) doubled that in 2017 (14.4%). The coinfection case rate also increased from 3.4% in 2016, 8.0% in 2017 to 16.1% in 2018. The high positive rate of PCV3 (56.9%) and PCV2 (33.8%) in oral fluids, PCV3 in foetuses (57.1%) and PCV2 in tonsils (54.8%) implied viral transmission route and tissue tropism. In phylogenetic analysis, two small PCV3 clusters (1 and 2) were separated but others were clustered with low bootstrapping values indicating overall low genetic diversity. Genotypes, PCV2a‐h, were confirmed by analysing 2, 944 strains, with a new genotype proposed as PCV2i. In this study, 61 PCV3 unique whole genomes were sequenced; 12 belonged to a separate cluster that were characterized by five consistent amino acid changes in the capsid protein (24V, 27K, 56D, 98R and 168K) and may be associated with potential differences in immunogenicity. Among the 43 unique PCV2 whole genomes sequenced, 31 belonged to PCV2d, 7 to PCV2a and 5 to PCV2b. Thus, our study demonstrates that PCV2d is the predominant genotype and PCV3 is widely circulating in the Midwest of the USA.